Purposive teaching styles for transdisciplinary AEC education: a diagnostic learning styles questionnaire - Syed Khuzzan Alhabshi, Sh Mazlina; Goulding, Jack Steven; Rahimian, Farzad Pour (Archnet-IJAR, 2015)
Acknowledging the progressive globalisation trend within the Architecture, Engineering, and Construction (AEC) industry, transdisciplinary education and training is now widely acknowledged as being one of the key factors for leveraging AEC organisational success. Conventional AEC education and training delivery approaches therefore need a paradigm shift in order to be able to address the emerging challenges of global practices. This study focuses on the use of Personalised Learning Environments (PLEs) to specifically address learners’ needs and preferences (learning styles) within managed Virtual Learning Environments (VLEs). This research posits that learners can learn better (and be more readily engaged in managed learning environments) with a bespoke PLE, in which the deployment of teaching and learning material is directly augmented towards their individual needs. In this respect, there is an exigent need for the Higher Educational Institutions (HEIs) to envelop these new approaches into their organisational learning strategy. However, part of this process requires decision-makers to fully understand the core nuances and interdependencies of functions and processes within the organisation, along with critical success factors and barriers. This paper presents findings from the development of a holistic conceptual Diagnostic Learning Styles Questionnaire (DLSQ) Framework, which is comprised of six interrelated dependencies (i.e. Business Strategy, Pedagogy, Process, Resources, Systems Development, and Evaluation). The confluence of these dependencies directly influences pedagogical effectiveness. These finding contribute additional understanding to the intrinsic nature of pedagogy in leveraging transdisciplinary AEC training within organisations (to improve learner effectiveness). This framework can help organisations better augment and align their strategic priorities to learner-specific traits. Keywords: Transdisciplinary learning; Personal Learning Environments (PLE); Diagnostic Learning Styles Questionnaire (DLSQ); pedagogical effectiveness; organisational drivers